Pengaruh Stabilitas Keuangan Dan Ketidakeffetifan Pengawasan Terhadap Kecurangan Laporan Keuangan yang dimoderasi oleh Penghindaran Pajak pada Bank Umum Syariah di Indonesia - Chairunisa, Mariyam (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2023)
This study examines the Effect of Financial Stability and Ineffective Supervision of Financial Statement Fraud moderated by Tax Avoidance at Islamic Commercial Banks in Indonesia in the 2016 – 2020 period. management as an agent with an investor as the principal which often benefits one party, resulting in Financial Statement Fraud. Earnings management as a way to commit financial statement fraud is carried out by the company so that the company looks better than its competitors so that investors who are less careful (inattentive investors) will become victims of the fraud. The research method used is the saturated sample method which uses secondary data in the form of annual reports of fourteen Islamic commercial banks in Indonesia that provide Annual Reports. The data obtained were processed by multiple linear regression analysis using SPSS statistical tools. The results of this study indicate that financial stability has a significant effect on financial statement fraud, while the ineffectiveness of supervision has no significant effect on financial statement fraud. The existence of tax avoidance as a moderating variable does not affect the relationship between the ineffectiveness of supervision on fraudulent financial statements.This research is expected to be a reference for further research.